Study on the Load Spectrum Test Method and Experiment of Shaft Parts of Loader - Wan Yipin; Jia Jie; Wei Yongxiang; Song Xuding (Jixie chuandong)
In order to obtain the load time history data of the shaft parts of loader drive system under the actual load,based on the load transfer principle and the design theory of the sensor,the load time history of shaft parts of the multi parameter test method is researched.Aiming at the key and difficult points of the load spectrum testing of the loader drive system,the dynamic telemetry device is used to solve the problem of parameter measurement in small space.The load signal acquisition system of loader shaft parts is established.And the system consisted of half shaft,drive shaft torque and speed parameters acquisition,engine speed parameters and the acquisition of gear parameters.The load time history data of the shaft parts are obtained by selecting the 50 type loader as the test sample.The test results show that the load test method is accurate and feasible,and the test method has very good generality and could be used for testing the load data of shaft parts of automobile,agricultural machinery and so on.